Tensile behaviour of transverse reinforcement with different connection methods in single steel-plate concrete composite structures. (May 2023) - Tang, Ruo-Yang; Nie, Xin; Ding, Ran; Sun, Yun-Lun; Fan, Jian-Sheng
Abstract: Transverse reinforcement is key to the single steel-plate concrete composite (SSC) structure when subjected to out-of-plane shear and impact load. This research focuses on the tensile behaviour of two connection methods between transverse reinforcement and steel plate in SSC structure, namely the tie bar interlocked with the J-hook connector (TBIJC) and the tie bar overlapped with the headed stud (TBOHS), which are much more convenient in construction compared to direct welding connection. Pull-out tests are carried out on 10 groups of specimens with different detail parameters to verify their reliable performance. Various types of failure modes and corresponding experimental phenomena are observed and recorded. The interfacial slip between the tie bar and concrete was measured to reflect the load–deflection characteristics. Parametric studies are carried out on the tensile performance considering connector shape and dimensions, end-anchor form of the tie bar and concrete strength. Plastic limit analysis is performed based on twin shear strength criterion for concrete, and an analytical model is developed to predict the ultimate tensile resistance. The accuracy of the proposed model is validated against the test results. Finally, based on the test results, design suggestions are proposed for the tie bar connection details considering both mechanical performance and construction efficiency.